PENGELOLAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERDESAAN DI DESA EMPIYANG - Aprilita Sapala E.42008015 (FISIP Universitas Tanjungpura Pontianak, 2013)
This writing is meant to describe and analyze Management of the National Program for Community Empowerment (PNPM Mandiri) in Sanggau Regency, especially at subdistric Jangkang, Empiyang village. The results of this research are: (1) planning process has doing well, but not fully get the active participation of the villagers, (2) the implementation process has been running with smoothly, but the planning process is to experience the quality of inhibitors of Human Resources (HR) low, facilities and infrastructure that have not been supportive, as well as methods that do not work right, (3) the regulatory process has been running from the beginning to the completion of the implementation activities, but this monitoring uncontinue after the completion of activities. Key Word : Management, Planning, Implementation, and Monitoring